Money Trumps Ethnicity: An Overview of Local Election in Kendari - Husain, M. Najib; Zuada, La Husen (UI Scholars Hub, 2021)
This paper explains how money politics and ethnic politics work at the same time, and which one of them is more influential when the two are confronted. By examining the 2017 regional election in the city of Kendari, this paper finds that both ethnic politics and money politics were used by contestants running in the election to gain voter support. Nevertheless, ethnic politics failed to maintain voter loyalty when contested with money politics that was designed carefully, massively, right on target, well-structured, and was supported by a solid and militant team.